Antimicrobial susceptibility, plasmid profiles, and RAPD-PCR typing of Acinetobacter bacteria. - Sadeghifard, Nourkhoda; Ranjbar, Reza; Zaeimi, Javad; Alikhan, Mohammad Yousef; Ghafouryan, Sobhan; Raftari, Mohammad; Abdulamir, Ahmed Sahib; Delpisheh, Ali; Mohebi, Reza; Abu Bakar, Fatimah (IOS Press, 2010)
Background: Multiple-drug resistant Acinetobacter have widely spread in the last decades imposing a serious nosocomial source of infection. Nevertheless, little knowledge was gaimed on tracing the development of antibiotic resistance in Acinetobacter species. Objectives: Explore Acinetobacter spp. via antimicrobial susceptibility, plasmid profiles, and random amplified polymorphism DNA polymerase chain reaction (RAPD-PCR) typing.Methods: One hundred twelve Acinetobacter isolates (including 66 A. baumannii and 46 non-Acinetobacter baumannii strains) were obtained from three university hospitals. The source of infection of these isolates included blood, urine, wound, and respiratory tract. Their susceptibilities to 17 antibiotics were tested and then all Acinetobacter isolates were typed by plasmid analysis and RAPD-PCR method.Results: A. baumannii isolates revealed nine different patterns of antibiotic resistance. Of those, non-A. baumannii, were associated with plasmid and RAPD-PCR typings (p 0.05).Conclusion: There is a wide spread of multi-drug resistant Acinetobacter spp., particularly A. baumannii, in the Middle East region that can be traced efficiently by plasmid and genotyping typing of Acinetobacter. More care should be taken for tracing the development of antimicrobial resistance of Acinetobacter using precise molecular typing techniques.